The fluidization dynamics of binary particles in a supergravity swirling liquid-solid fluidized bed using coupled MPPIC-VOF approach - Hailong Tang; Jingfeng He; Liangyu Yao; Dongyao Wang; Lixiang Fu; Bin Yang; Lingtao Zhu; Yuhao Liu (Chemical Engineering Journal, 2026)

Multifunctional aramid honeycombs filled with PVDF composite foams via in situ supercritical foaming: Nearly-isotropic broadband microwave absorption and mechanical reinforcement - Yang Ou; Hongbo Hou; Jingfeng He; Wenhan Cui; Jiaju Zhu; Li Ma; Fanbin Meng (Chemical Engineering Journal, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

Evolution characteristics and energy loss of the swirling flow in a gradient supergravity rotating field used for separation - Hailong Tang; Jingfeng He; Liangyu Yao; Lixiang Fu; Bin Yang; Lingtao Zhu (Journal of Environmental Chemical Engineering, 2026)

Optimization of friction medium rod shape and its enhanced pre-concentration of coal-hosted graphite ore by triboelectric separation - Yuhao Liu; Jingfeng He; Wenjie Tang; Shuaixing Shi; Lingtao Zhu; Bin Yang (Minerals Engineering, 2026)

Multidrug-resistant plasmid modulates ammonia oxidation efficiency in Nitrosomonas europaea through cyclic di-guanylate and acyl-homoserine lactones pathways - Jinrui Cao; Chen Zhao; Lin Bo; Xinxin He; Yuchao Liu; Shang Wang; Bin Xue; Jingfeng Wang (Bioresource Technology, 2026)

Temporal Memory Mechanisms and Biome‐Specific Drivers of Ecosystem Carbon Flux: Insights From Explainable Deep Learning Modeling - Teng Ma; Wei He; Shuangxi Fang; Jingfeng Xiao; Ngoc Tu Nguyen; Hua Yang; Peipei Xu; Chengcheng Huang; Mengyao Zhao; Shuai Liu; Xinhui Lei; Ziyi Huang (Global Change Biology, 2026)
Ecosystem carbon dynamics are governed by complex temporal dependencies and environmental interactions, yet these processes remain poorly understood and quantified across diverse biomes. Here, we developed an explainable LSTM‐Attention framework that integrates LSTM networks, attention mechanisms, and gradient‐based attribution methods to reveal temporal dependencies in ecosystem carbon flux responses by analyzing eddy covariance flux measurements from 71 sites spanning eight North American biomes. Using this approach, we identified three distinct temporal memory patterns governing carbon flux responses. Grasslands exhibit short‐term memory dominance with exponentially increasing temporal contributions from distant to recent past. Deciduous broadleaf forests and wetlands show long‐term memory dominance, with deciduous broadleaf forests displaying the strongest historical dependence (attribution values declining from 0.30 at 6 months to 0.045 at 1 month). Croplands and evergreen needleleaf forests demonstrate U‐shaped dual memory patterns. Building on these temporal patterns, we identified biome‐specific environmental drivers operating within each memory framework: wetlands primarily controlled by soil moisture, evergreen needleleaf forests by radiation, and closed shrublands by vapor pressure deficit. Beyond individual drivers, we uncovered critical nonlinear interactions that diverged from linear correlations at most sites (55 of 71 with ρ

Transcriptome and metabolome analyses revealed mechanisms underlying vernalization-induced bolting in two contrasting genotypes of cabbage (Brassica oleracea var. capitata) - Huiju Yang; Jingfeng Hu; Mingwei Chen; Mei Lan; Jiangming He (Journal of Plant Biochemistry and Biotechnology, 2025)

A strategy for effective flocculation and sedimentation of coal gasification fine slag using a composite reagent system of CTAC/PDADMAC/NPAM - Jiawei Wu; Jingfeng He; Xinyao Wang; Hailong Tang; Bin Yang; Lingtao Zhu (Journal of Water Process Engineering, 2025)

Coupled retrieval of turbulent heat fluxes and gross primary productivity via the assimilation of land surface temperature data from geostationary satellites - Zongbin Xu; Tongren Xu; Xinlei He; Jingfeng Xiao; Sayed M. Bateni; Changhyun Jun; Gangqiang Zhang; Wenting Ming; Shaomin Liu (Remote Sensing of Environment, 2025)

Supergravity separation: An innovative strategy for efficient cleaning and upgrading of coal gasification slag waste - Hailong Tang; Jingfeng He; Lixiang Fu; Jiahui Zhang; Liangyu Yao; Bin Yang; Lingtao Zhu; Shihai Guo (Waste Management, 2025)

Microplastics enhance the denitrification of glycogen-accumulating organisms by regulating electronic transport in carbon-nitrogen coupling - Yuchao Liu; Jinrui Cao; Sheng Li; Xinxin He; Bin Zhang; Shang Wang; Jingfeng Wang (Journal of Hazardous Materials, 2025)

Relic DNA obscures bacterial diversity and interactions in ballast tank sediment - Zhaozhao Xue; Haoze He; Yangchun Han; Wen Tian; Shengjie Li; Jingfeng Guo; Pei Yu; Lina Qiao; Wei Zhang (Environmental Research, 2025)

Environmental RNA metabarcoding for ballast water microbial diversity: Minimizing false positives - Zhaozhao Xue; Wen Tian; Yangchun Han; Shengjie Li; Jingfeng Guo; Haoze He; Pei Yu; Wei Zhang (Science of The Total Environment, 2024)

Efficient extraction of rare earth elements from coal-series kaolin by combining alkali fusion and sulfamic acid leaching - Lingtao Zhu; Jingfeng He; Linghua Chen; Bin Yang (Process Safety and Environmental Protection, 2024)

Global convergence in terrestrial gross primary production response to atmospheric vapor pressure deficit - Chao Huang; Jingfeng Huang; Jingfeng Xiao; Xing Li; Hong S. He; Yu Liang; Fusheng Chen; Hanqin Tian (Science China Life Sciences, 2024)

Cleaning and upgrading of low-rank coal using a novel rotary triboelectric separator with the polyvinyl chloride as friction medium - Bin Yang; Lingtao Zhu; Jingfeng He; Bin Liu; Shibo Huang; Hao Chen; Wenjie Tang (Fuel, 2024)

Multidrug-resistant plasmid RP4 inhibits the nitrogen removal capacity of ammonia-oxidizing archaea, ammonia-oxidizing bacteria, and comammox in activated sludge - Zhaohui Zhang; Lin Bo; Shang Wang; Chenyu Li; Xi Zhang; Bin Xue; Xiaobo Yang; Xinxin He; Zhiqiang Shen; Zhigang Qiu; Chen Zhao; Jingfeng Wang (Environmental Research, 2024)

Multidrug-resistant plasmid RP4 increases NO and N2O yields via the electron transport system in Nitrosomonas europaea ammonia oxidation - Jia Li; Chen Zhao; Chenyu Li; Bin Xue; Shang Wang; Xi Zhang; Xiaobo Yang; Zhiqiang Shen; Lin Bo; Xinxin He; Zhigang Qiu; Jingfeng Wang (Water Research, 2023)

Study on integration of drying and separation for lignite by hot airflow gas–solid fluidized bed - Jingfeng He; Qingyao Yao; Mingming Zhang; Bin Yang; Lingtao Zhu; Hao Chen; Xin Zhang (Fuel, 2023)

Surface modification to enhance the decarbonization performance of coal-series kaolin by triboelectric separation - Jingfeng He; Xin Zhang; Qiang Bai; Shibo Huang; Hao Chen; Chengjing Guo; Lingtao Zhu; Bin Yang (Applied Clay Science, 2023)

Efficient recovery of valuable metals from waste printed circuit boards via ultrasound-enhanced flotation - Linghua Chen; Jingfeng He; Lingtao Zhu; Qingyao Yao; Youbang Sun; Chengjing Guo; Hao Chen; Bin Yang (Process Safety and Environmental Protection, 2023)

A novel utilization of raw sepiolite: preparation of magnetic adsorbent directly based on sol–gel for adsorption of Pb(II) - Jiang Xu; Jingfeng He; Lingtao Zhu; Shulian Guo; Hao Chen (Environmental Science and Pollution Research, 2022)

Aberrant DNA methylation in t(8;21) acute myeloid leukemia - Shujiao He; Jingfeng Zhou; Li Yu (Genome Instability & Disease, 2022)
Aberrant DNA methylation is a hallmark of acute myeloid leukemia (AML). Various studies showed that t(8;21) AML presented a distinct DNA methylation profile and could be categorized into a separate cluster according to DNA methylation sequencing. Yet, there is still a lack of understanding regarding the causes and mechanisms of this phenomenon. Knowing how the DNA methylation is regulated in t(8;21) AML would enhance our understanding of leukemogenesis and may assist clinical decision-making regarding DNA methylation-targeted therapy. Herein, we summarized our current knowledge concerning DNA methylation regulation in t(8;21) AML and discussed their potential clinical significance in this article.

PFC2D-based investigation on the mechanical behavior of anisotropic shale under Brazilian splitting containing two parallel cracks - Bo He; Jun Liu; Peng Zhao; Jingfeng Wang (Frontiers of Earth Science, 2021)

Spatial econometric analysis of carbon emission intensity in Chinese provinces from the perspective of innovation-driven - Song Liang; Jingfeng Zhao; Shumin He; Qingqing Xu; Xin Ma (Environmental Science and Pollution Research, 2019)

Solar‐induced chlorophyll fluorescence exhibits a universal relationship with gross primary productivity across a wide variety of biomes - Jingfeng Xiao; Xing Li; Binbin He; M. Altaf Arain; Jason Beringer; Ankur R. Desai; Carmen Emmel; David Y. Hollinger; Alisa Krasnova; Ivan Mammarella; Steffen M. Noe; Penélope Serrano Ortiz; et al. (Global Change Biology, 2019)

Solar‐induced chlorophyll fluorescence is strongly correlated with terrestrial photosynthesis for a wide variety of biomes: First global analysis based on OCO‐2 and flux tower observations - Xing Li; Jingfeng Xiao; Binbin He; M. Altaf Arain; Jason Beringer; Ankur R. Desai; Carmen Emmel; David Y. Hollinger; Alisa Krasnova; Ivan Mammarella; Steffen M. Noe; Penélope Serrano Ortiz; et al. (Global Change Biology, 2018)
Solar‐induced chlorophyll fluorescence (SIF) has been increasingly used as a proxy for terrestrial gross primary productivity (GPP). Previous work mainly evaluated the relationship between satellite‐observed SIF and gridded GPP products both based on coarse spatial resolutions. Finer resolution SIF (1.3 km × 2.25 km) measured from the Orbiting Carbon Observatory‐2 (OCO‐2) provides the first opportunity to examine the SIF–GPP relationship at the ecosystem scale using flux tower GPP data. However, it remains unclear how strong the relationship is for each biome and whether a robust, universal relationship exists across a variety of biomes. Here we conducted the first global analysis of the relationship between OCO‐2 SIF and tower GPP for a total of 64 flux sites across the globe encompassing eight major biomes. OCO‐2 SIF showed strong correlations with tower GPP at both midday and daily timescales, with the strongest relationship observed for daily SIF at the 757 nm ( R 2 = 0.72, p R 2 = 0.57–0.79, p R 2 = 0.16, p 4 grasslands and croplands than for C 3 ecosystems. The generally consistent slope of the relationship among biomes suggests a nearly universal rather than biome‐specific SIF–GPP relationship, and this finding is an important distinction and simplification compared to previous results. SIF was mainly driven by absorbed photosynthetically active radiation and was also influenced by environmental stresses (temperature and water stresses) that determine photosynthetic light use efficiency. OCO‐2 SIF generally had a better performance for predicting GPP than satellite‐derived vegetation indices and a light use efficiency model. The universal SIF–GPP relationship can potentially lead to more accurate GPP estimates regionally or globally. Our findings revealed the remarkable ability of finer resolution SIF observations from OCO‐2 and other new or future missions (e.g., TROPOMI, FLEX) for estimating terrestrial photosynthesis across a wide variety of biomes and identified their potential and limitations for ecosystem functioning and carbon cycle studies.

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Survival and development of Liaodong oak stump sprouts in the Huanglong Mountains of China six years after three partial harvests - Li Rong; Zhang Wenhui; He Jingfeng; Zhou Jianyun (New Forests, 2013)

Total body irradiation of donors can alter the course of tolerance and induce acute rejection in a spontaneous tolerance rat liver transplantation model - YeWei Zhang; HeWei Zhao; Lin Bo; YinXue Yang; Xiang Lu; JingFeng Sun; JianFei Wen; Xia He; GuoWen Yin (Science China Life Sciences, 2012)

Effects of Epstein-Barr virus infection on the development of multiple myeloma after liver transplantation - YeWei Zhang; HeWei Zhao; Xia He; SuWen Zheng; TaiHong Wang; DongLiang Yan; JingFeng Sun; Xiang Lu; JianFei Wen; Wan Yee Lau (Science China Life Sciences, 2012)

Functional study of immature dendritic cells co-transfected with IL-10 and TGF-beta 1 genes in vitro - Lihong Chen; Minglian Qiu; Wubing He; Aimin Huang; Jingfeng Liu (Molecular Biology Reports, 2012)